Preliminary view of geotechnical properties of soft rocks of Semanggol formation at Pokok Sena, Kedah - Ahmad, N.R. (Institute of Physics Publishing, 2018)
The research was inspired by series of geological studies on Semanggol formation found exposed at North Perak, South Kedah and North Kedah. The chert unit comprised interbedded chert-shale rocks are the main lithologies sampled in a small-scale outcrop of Pokok Sena area. Black shale materials were also observed associated with these sedimentary rocks. The well-known characteristics of shale that may swell when absorb water and leave shrinkage when dried make the formation weaker when load is applied on it. The presence of organic materials may worsen the condition apart from the other factors such as the history of geological processes and depositional environment. Thus, this research is important to find the preliminary relations of the geotechnical properties of soft rocks and the geological reasoning behind it. Series of basic soil tests and 1-D compression tests were carried out to obtain the soil parameters. The results obtained gave some preliminary insight to mechanical behaviour of these two samples. The black shale and weathered interbedded chert-shale were classified as sandy-clayey-SILT and clayey-silty-SAND respectively. The range of specific gravity of black shale and interbedded chert/shale 2.3 - 2.6 and fall in the common range of shale and chert specific gravity value. In terms of degree of plasticity, the interbedded chert/shale samples exhibit higher plastic degree compared to the black shale samples. Results from oedometer tests showed that black shale samples had higher overburden pressure (Pc) throughout its lifetime compare to weathered interbedded chert-shale, however the compression index (Cc) of black shale were 0.15 - 0.185 which was higher than that found in interbedded chert-shale. The geotechnical properties of these two samples were explained in correlation with their provenance and their history of geological processes involved which predominantly dictated the mechanical behaviour of these two samples. Â© 2018 Published under licence by IOP Publishing Ltd.